The construction of personal and professional boundaries in Australian social work: a qualitative exploration of the self in practice - Zubrzycki, Joanna (Curtin University, 2003)
The boundary between the personal and the professional self is a site of professional and personal creativity and tension, a space that reflects some of the key ontological and epistemological issues confronting social work. Exploring the social construction of the self through the stories of fifteen Australian social workers brings these issues into stark relief. The participatory and reflexive research process facilitated the development of knowledge about how a group of culturally diverse social workers construct personal and professional boundaries in practice.The need to explore these processes and relationships was predicated on a concern that while the self is generally recognised as shaping practice, there has been a paucity of attention given to what lived experiences constitute the self. Social work practice is broadly defined as a socially constructed profession, yet the personal and professional boundary is regarded as individually constructed and defined. This discourse neglects the influence of contextual, cultural, relational and structural dimensions of the self, thus denying the possibilities of practice being continually informed by a myriad of experiences.Recognising that the socially constructed self is situated within intersections of knowledge and meaning opens up possibilities for the development of dialogical practices within an ethics of care. The research also has implications for social work practice and education and for the way that we supervise and manage social work staff. Professional dialogue, debate and practice needs to reflect a diversity of experiences and recognise that the dominant discourse about boundaries and the self leaves many workers feeling that their practice reality is not a shared one.